2008
DOI: 10.1007/s10557-008-6154-3
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra in Experimental Acute Myocardial Infarction—Does Dosage or Duration of Treatment Matter?

Abstract: Anakinra inhibits apoptosis and ameliorates cardiac remodeling up to 4 weeks after infarction. A 2-week regimen is superior to a 1-week regimen, whereas a higher dose did not provide any further benefit over standard doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…In this model, we found that time of treatment was sufficient to reduce adverse remodeling in the long term without rebound effects due to interruption of the treatment (37,38). However, considering that anakinra preserved the contractile reserve at 3 d but not at 4 months, we speculate that a longer treatment with anakinra may be needed.…”
Section: Discussionmentioning
confidence: 76%
“…In this model, we found that time of treatment was sufficient to reduce adverse remodeling in the long term without rebound effects due to interruption of the treatment (37,38). However, considering that anakinra preserved the contractile reserve at 3 d but not at 4 months, we speculate that a longer treatment with anakinra may be needed.…”
Section: Discussionmentioning
confidence: 76%
“…A role of apoptosis, an immunologically silent cell-death form, in myocardial IRI has been repeatedly proposed, but these studies have typically used terminal deoxynucleotidyltransferasemediated dUTP nick end labeling assay, which is not specific for apoptosis and additionally detects pyroptosis and other cell-death forms. 4,5,17,19 Our in vivo kinetic studies demonstrate that inflammasome activation precedes apoptosis (Figure 2). Additionally, Nlrp3 deficiency is protective in myocardial IRI.…”
Section: 5152mentioning
confidence: 75%
“…Several groups have shown that inflammasome inhibition improves cardiac remodeling and function at later time points. 4,5,67 Because aPC ameliorates angiotensin II-triggered myocardial remodeling, 22 an improved outcome after aPC-mediated inflammasome restriction seems conceivable, but this remains to be shown.…”
Section: 5152mentioning
confidence: 99%
See 1 more Smart Citation
“…24) IL-1Ra has been shown to have a cardioprotective function. [25][26][27][28] Although the cardioprotective effects of hexarelin have been partially revealed by many studies, the action of hexarelin on myocardial I/R injury in vivo have not been fully confirmed, whereas the underlying mechanisms remain unknown. In our study, using rat models of myocardial I/R, we attempted to observe the effects of hexarelin treatment on myocardial I/R injury, as well as clarify the role of the IL-1 signaling pathway in the cardiovascular action of hexarelin.…”
mentioning
confidence: 99%